CARACTERIZAÇÃO AGRONÔMICA E BROMATOLÓGICA DA FORRAGEM DE TOPCROSSES DE LINHAGENS S3 DE MILHO EM DIFERENTES ESPAÇAMENTOS - GABRIEL, ANDRÉ (2015)
The objective of this study was to evaluate the performance of topcrosses hybrid of partially inbred lines (S3) of corn from three populations crossed with narrow genetic base tester (DKB245), as the agronomic traits, grain yield and productive characters and Bromatological the whole plant forage maize in two row spacings. Three commercial corn hybrids (P30B39, AS1572 and SG6015) were used for the generation of populations, designated 102, 103 and 203, respectively, from which was obtained 25 S3 lines of each population. Two contiguous experiments were conducted in triple lattice design 9 x 9. In the first experiment the line spacing was 0.4m in the second was 0.7 me getting the final density of 70,000 plants ha-1 in both experiments. Significant effects for the source of variation 'genotypes' for all evaluated characteristics. Significant effects for the source of variation 'environments' for silage cutting point, stay green, percentage of dry matter and green mass productivity. Interaction 'genotype x environment' was significant for other agronomic traits. The topcrosses hybrid HTC103-15 and HTC203-01 stood out with the lowest fiber content insoluble in acid detergent insoluble fiber in neutral detergent, for superior performance relative value of fodder and in situ digestibility of the whole plant. The hybrid topcross HTC102-21 stood out for the characteristics of dry matter yield, fiber content insoluble in acid detergent insoluble neutral detergent fiber and grain yield. The hybrid DKB245 (tester) was useful for distinguishing the relative merit of S3 lines of maize to the qualitative characteristics of the whole plant for forage.